An Update on Biochemical and Genomic Markers for Prostate Cancer: Biochemical and Genomic Markers for Prostate Cancer - Falahatkar, Reza; Mokhtari, Gholamreza; Momeni-Moghaddam , Madjid; Teimoori, Mojtaba; Baghani Aal , Hamidreza; Akhavan, Ardalan; Falahatkar, Siavash; Esmaeili, Samaneh (Urology Journal, 2021)
Purpose: Detecting prostate cancer, developing therapeutic plans after negative biopsies, and prognosis-based patient counseling can be challenging for many urologists dealing with prostate cancer-specific antigens. New Biomarkers advances made improvement for prediction of responses to therapeutic option and can tell us about survival and recurrence. In this review, we have assessed current and upcoming biomarkers that are opening a new era in diagnosing the disease. Materials and Methods: We conducted a comprehensive literature review of studies describing prostate cancer biomarkers. Two independent investigators searched PubMed, Embase, Web of Science, and Cochrane Databases to identify biomarkers in prostate cancer conducted a literature review. Results: Recently, combining prostate cancer-specific biomarkers into a single test has gained increasing attention, especially since the introduction of genomic and molecular tools. The development of the Prostate Health Index (PHI), SelectMDx, and Confirm MDx have shown promising results for prostate cancer detection, in addition to risk stratification and biopsy avoidance. Conclusion: Despite major improvements and innovations in prostate cancer biomarkers, application in current clinical practice is limited. However, these biomarkers have an important role in determining risk, preventing unnecessary prostate biopsies, and predicting prognoses. Additional confirmatory studies will be needed to fully understand the impact of prostate cancer-specific biomarkers.